A catered thanksgiving ebook - Crawford, Isis (A Mystery with Recipes, 2010)
A dysfunctional family holiday turns deadly in this "sprightly" mystery ( Publishers Weekly ). Whipping up Thanksgiving dinner can be stressful for anyone, but that goes double for the Field family. Everything has to be perfect, or they risk getting cut out of dominating patriarch Monty's lucrative will. That's where sisters Bernie and Libby's catering company, A Little Taste of Heaven, comes in. Surely with their lumpless mashed potatoes and to-die-for gravy, even the super-dysfunctional Fields can get along for one meal. But no one can dress up disaster when the turkey goes boom right in Monty's scowling face, sending him to that great dining room in the sky. With everyone harboring their own cornucopia of secrets, discovering who wanted to carve up Monty won't be easy. Worse, the Field Mansion is draped under a snowstorm, trapping them with a killer determined to get more than his piece of the pie. Bernie and Libby will have to find out who the culprit is, fast, before the leftovers—and their chances of surviving—run out for good... Includes tasty recipes! "Fans of culinary cozies by Joanne Fluke and Diane Mott Davidson will enjoy discovering Crawford." – Library Journal